ANALISIS MANAJEMEN RISIKO TERHADAP PEKERJAAN PRASARANA JALAN PADA PROGRAM PEMBERDAYAAN MASYARAKAT (PRODAMAS PLUS) KOTA KEDIRI (Jurnal Spesialis Teknik Sipil (JSpTS), 2021)
The Community Empowerment Program Plus or abbreviated as Prodamas Plus is a program from the Kediri City Government for each RT in the Kediri City area, because this program is directly carried out by the community, so various risks arise from the planning stage, implementation to accountability reports, especially in the field of road infrastructure, therefore it is necessary to know the level of the risks that arise in order to facilitate the determination of the right response. The technique for identifying risk uses a literature study, which is then validated by experts and a questionnaire on 30 selected respondents to obtain data on the frequency and impact of risk on a linkert scale. Results of the questionnaire Then a risk analysis was carried out using the Analytical Hierarchy Process (AHP) method. After knowing the dominant risk factors, then a risk response analysis is carried out with expert validation to determine the right response. Of the 33 risk variables, the expert validation results obtained the most dominant risk variable, namely the competence of the companion is not good. Furthermore, from the experts obtained response recommendations for dominant risks, namely preventive strategies by selecting to produce assistants who have the ability in the fields of construction, administration, communication and have a good work ethic and corrective strategies by conducting training to assistants.